A new modification of the Passerini reaction: a one-pot synthesis of α-acyloxyamides via sequential Kornblum oxidation/Passerini reaction. Issue 15 (8th April 2015) - Adib, Mehdi; Sheikhi, Ehsan; Azimzadeh, Marjan
Graphical abstract: Abstract: A novel approach for the synthesis of α-acyloxyamides is described. Benzylic substrates (halides or tosylates), under mild Kornblum conditions, are oxidized to give the corresponding aldehydes, which undergo a Passerini reaction with carboxylic acids and isocyanides to produce the corresponding α-acyloxyamides in excellent yields.